2006
DOI: 10.1007/s00531-006-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Miocene tectonics of the Maramures area (Northern Romania): implications for the Mid-Hungarian fault zone

Abstract: The interplay between the emplacement of crustal blocks (e.g. ''ALCAPA '', ''Tisza'', ''Dacia'') and subduction retreat is a key issue for understanding the Miocene tectonic history of the Carpathians. Coeval thrusting and basin formation is linked by transfer zones, such as the Mid-Hungarian fault zone, which seperates ALCAPA from Tisza-Dacia. The presented study provides new kinematic data from this transfer zone. Early Burdigalian (20.5 to~18.5 Ma) SE-directed thrusting of the easternmost tip of ALCAPA (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 39 publications
2
64
0
1
Order By: Relevance
“…Their emplacement was controlled by sinistral transtensional stress regimes at 12-10 Ma along an transcurrent fault system and oblique convergence of Tisia-Dacia with the NW-SE striking European margin [339]. The spatial distribution of intrusive bodies however is not along the main trace of the transcurrent fault.…”
Section: ţIbleș -Rodnamentioning
confidence: 99%
“…Their emplacement was controlled by sinistral transtensional stress regimes at 12-10 Ma along an transcurrent fault system and oblique convergence of Tisia-Dacia with the NW-SE striking European margin [339]. The spatial distribution of intrusive bodies however is not along the main trace of the transcurrent fault.…”
Section: ţIbleș -Rodnamentioning
confidence: 99%
“…Due to the lack of exposures in the majority of the Pannonian Basin, the exact surface position and structural style of the MHL still raises questions. Only at the Poiana Botizii area, the assumed eastern termination of the MHL (Balla 1984;Csontos et al 1992;Győrfi et al 1999;Tischler et al 2007) can the contact be directly observed: here ALCAPA is thrust over Tisza-Dacia. The affiliation of the zone near its assumed western end, close to Zagreb, is also debated (Tari & Pamić 1998;Tomljenović & Csontos 2002).…”
Section: Geological Settingmentioning
confidence: 99%
“…Márton & Már-ton 1978, 1996Márton & Fodor 1995Panaiotu 1998, mega-tectonic units were internally deformed. This is particularly true for their contact zone, the Mid-Hungarian fault zone, which continues into Northern Romania (Csontos & Nagymarosy 1998, Fodor et al 1999, Tischler et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Csontos & Nagymarosy 1998, Tischler et al 2007) along the Mid-Hungarian fault zone. The Mid-Hungarian fault zone shows a polyphase history, allowing for repeatedly occurring differential movements between the invading mega-tectonic units (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation